1984
DOI: 10.1152/ajprenal.1984.247.3.f499
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptors in the proximal tubule of the rabbit

Abstract: Our laboratory has characterized dopamine receptors in glomeruli and tubular homogenates. Since the heterogeneity of kidney homogenates limits the interpretation of these studies, the [3H]haloperidol binding site and adenylate cyclase sensitivity to dopamine were studied in the isolated proximal convoluted tubule and pars recta of the rabbit kidney. [3H]Haloperidol binding sites were saturable, stereoselective, and of high affinity. The apparent dissociation constant was 31.5 X 10(-9) M (+/- 8.5) and the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…This may be due to high intrarenal concentrations of dopamine overcoming the DA1-receptor antagonism in a competitive manner with time. This may occur preferentially at the proximal tubular receptors (Felder et al, 1984) close to the site at which dopamine is thought to be generated (Hagege & Richet, 1985) and secreted (Baines & Chan, 1980). Serum sulpiride concentrations were falling throughout the gludopa infusion and may have contributed to an increasing effect of gludopa.…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to high intrarenal concentrations of dopamine overcoming the DA1-receptor antagonism in a competitive manner with time. This may occur preferentially at the proximal tubular receptors (Felder et al, 1984) close to the site at which dopamine is thought to be generated (Hagege & Richet, 1985) and secreted (Baines & Chan, 1980). Serum sulpiride concentrations were falling throughout the gludopa infusion and may have contributed to an increasing effect of gludopa.…”
Section: Discussionmentioning
confidence: 97%
“…Early in vivo studies suggested that dopamine may also exert specific effects on tubular salt handling (McGiff & Bums, 1967) and this question has more recently been addressed by in vitro tubular preparation techniques. Dopamine receptors have been identified on proximal tubular cells (Felder et al, 1984) and Bello-Reus et al (1982) . Dopamine stimulates cAMP synthesis in the rat kidney particulate preparation (Nakajima et al, 1977) and an increase in urine cAMP has been measured after dopamine infusion in man (Vlachoyannis et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…PCT was microdissected from male 18-20-wk-old SHR (mean arterial pressure 166.6±2.7 mmHg, n = 9) and WKY (mean arterial pressure 11 1.3±1.5 mmHg, n = 9) (Harlan-Sprague Dawley, Inc., Indianapolis, IN) according to the procedure previously described from this laboratory (17,18). In a separate group of experiments 3-wk-old WKY and SHR were used.…”
Section: Dissection Ofproximal Convoluted Tubulesmentioning
confidence: 99%
“…We have previously reported the presence of DA-1 receptors coupled to stimulation of adenylate cyclase in the PCT of the rabbit ( 17) and rat kidney ( 18). These receptors are also present in proximal straight tubule (17)(18)(19)(20) and cortical collecting duct (16,19).…”
Section: Introductionmentioning
confidence: 99%